Hemorrhage and secondary infection of an infantile hemangioma during involution: A case report. Issue 5 (6th May 2021) - Gardner, James Reed; Fuller, Colin; Johnson, Adam B.
Abstract : Bleeding complications due to IHs are generally limited. Secondary abscess formation after hemorrhage has not been reported. Rapid expansion of an IH should raise concern for hemorrhage in IHs that have been an involutionary phase.